Stakeholder perspectives on COVID-19 and household water access in vulnerable communities in the Mekong Region - Lebel, L.; Aung, N.; Long, C. T. M.; Siharath, P.; Lebel, P.; Navy, H.; Hoanh, Chu Thai; Lebel, B. (Springer, 2022)
The COVID-19 pandemic has underlined the importance of safe access to sufficient clean water in vulnerable communities, renewing interest in water, sanitation and hygiene (WASH) programs and related targets under Sustainable Development Goal 6 (SDG 6). The purpose of this study was to better understand the obstacles to water access in vulnerable communities and identify ways they might be addressed in five countries in the Mekong Region (Cambodia, Laos, Myanmar, Thailand, Vietnam). To this end, qualitative interviews with 50 government officials and development or health experts were complimented with a quantitative survey of the experiences and views of individuals in 15 vulnerable communities. There were several key findings. First, difficulties in accessing sufficient clean water for drinking and hygiene persist in certain vulnerable communities, including informal urban settlements, remote minority villages, and migrant worker camps. Second, limited rights, high prices, and remote locations were common obstacles to household access to improved water sources. Third, seasonal differences in the availability of clean water, alongside other disruptions to supply such as restrictions on movement in COVID-19 responses, drove households towards lower quality sources. Fourth, there are multiple threats to water quality from source to consumption that should be addressed by monitoring, treatment, and watershed protection. Fifth, stakeholder groups differ from each other and residents of vulnerable communities regarding the significance of water access, supply and quality difficulties, and how they should be addressed. The paper ends with a set of program suggestions addressing these water-related difficulties.